2010
DOI: 10.1093/hmg/ddq077
|View full text |Cite
|
Sign up to set email alerts
|

Uromodulin is expressed in renal primary cilia and UMOD mutations result in decreased ciliary uromodulin expression

Abstract: Uromodulin (UMOD) mutations are responsible for three autosomal dominant tubulo-interstitial nephropathies including medullary cystic kidney disease type 2 (MCKD2), familial juvenile hyperuricemic nephropathy and glomerulocystic kidney disease. Symptoms include renal salt wasting, hyperuricemia, gout, hypertension and end-stage renal disease. MCKD is part of the 'nephronophthisis-MCKD complex', a group of cystic kidney diseases. Both disorders have an indistinguishable histology and renal cysts are observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 64 publications
(68 reference statements)
1
46
1
3
Order By: Relevance
“…It is a highly glycosylated protein processed in the endoplasmic reticulum (ER) and Golgi apparatus, translocated to the luminal cell membrane, and released in the urine by proteolytic cleavage. So far, Ͼ70 different UAKDcausing UMOD mutations have been published, of which all but four (in-frame deletions) lead to amino acid substitutions (4,7,11). Mutant uromodulin isoforms exhibit a protein maturation defect and are retained in the ER (12,13).…”
Section: Uromodulin-associated Kidney Disease (Uakd)mentioning
confidence: 99%
“…It is a highly glycosylated protein processed in the endoplasmic reticulum (ER) and Golgi apparatus, translocated to the luminal cell membrane, and released in the urine by proteolytic cleavage. So far, Ͼ70 different UAKDcausing UMOD mutations have been published, of which all but four (in-frame deletions) lead to amino acid substitutions (4,7,11). Mutant uromodulin isoforms exhibit a protein maturation defect and are retained in the ER (12,13).…”
Section: Uromodulin-associated Kidney Disease (Uakd)mentioning
confidence: 99%
“…New insight into the pathophysiology of UAKD has been provided by recent reports linking uromodulin to the central apical cilium of TAL cells and demonstrating decreased ciliary uromodulin expression in biopsy tissue from UAKD patients [32], suggesting that UAKD belongs to the group of diseases termed "ciliopathies." This group includes polycystic kidney diseases (PKD) and nephronophthisis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…After proper folding, modification with high mannose glycomoieties, and addition of a C-terminal glycophosphatidylinositol, the protein exits the rough ER and transits to the Golgi apparatus where it is further modified with complex-type carbohydrates and then destined for the apical plasma membrane (5,6). Mature THP is believed to anchor via its glycophosphatidylinositol tail onto the luminal leaflet of the lipid bilayer of the apical membrane of the thick ascending limb of the loop of Henle, although a recent study found the protein also to be associated with the primary cilia and the mitotic spindle poles of these tubular cells (7). Apically located THP is eventually released by proteases and/or phospholipases into the urine where it constitutes the most abundant urinary protein in most mammals (8 -10).…”
mentioning
confidence: 99%